FENOMENA IBU DALAM KARYA SENI LUKIS SUREALIS - Rahmat Hidayat, Drs. Abd. Hafiz, M.Pd, Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2017)
The purpose of this final project is to realize the phenomenon of mothers in the form of metaphors herbs and natural objects in the works of surrealist art. The author presents the concept of the creation of works relating to the method of creating the work through the stages of exploration, the incubation phase, experimentation, improvisation, stage of elaboration, the embodiment of the idea and the realization of the concept, that is the beginning of the cultivation phase, the process of finishing, and the presentation of the work. Ten patterned surrealist painting that describes the phenomenon of the mother. The tenth of the work include: 1). The Keeper, 2). Staring future, 3). The Pelita, 4). Super Mom, 5). Mother, 6). Remove the Hand, 7). Survive, 8). Tough, 9). Glamour, 10) .Ibu II. The painting will appreciate the role of the mother is very important.Keywords: Phenomena, Mother, Surrealist Painting.